Cover, Content, and Editorial Note from Borneo J Pharm Vol. 5 No. 4 November 2022 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2022)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm) has been published in November 2022. This edition contains ten articles: Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Microbiology Pharmacy, Natural Product Development, and Clinical-Community Pharmacy. This edition includes writings from three countries: China, Indonesia, and Nigeria. The authors come from several institutions, including IPB University, Universitas Pembangunan Nasional Veteran Jakarta, Universitas Pelita Harapan, Adamawa State Polytechnic, Modibbo Adama University of Technology, Yola, Universitas Abdurrab, Universitas Gadjah Mada, Universitas Borneo Lestari, Universitas Airlangga, Universitas Islam Negeri Maulana Malik Ibrahim Malang, National Research and Innovation Agency Republic of Indonesia, Kebbi State University of Science and Technology, Aliero, Institut Sains dan Teknologi Nasional, Sekolah Tinggi Ilmu Farmasi Makassar, Universitas Ahmad Dahlan, and The First Affiliated Hospital of Nanjing Medical University. Editorial boards are fully aware that there is still room for improvement in this edition; hence with all humility, willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors, can re-participate for publication in the next edition on February 2023. Wassalamu’alaikum Wr. Wb.